SISTEM INFORMASI PENGOLAHAN DATA NILAI BERBASIS MULTIUSER PADA STIKES KARYA HUSADA SEMARANG - Nikmatul Khasanah (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2018)
STIKES Karya Husada Semarang, located on Jl. Intan Raya No.1, STIKES Karya Husada Semarang in processing data values ​​using Microsoft Excel so that the data storage has not been integrated because it is still individually not stored in one database and can only be accessed by 1 user. Fast and accurate information is really needed by STIKES in delivering information. To overcome the problems at STIKES Karya Husada Semarang, information systems need to be fast and accurate in conveying information. One information system that can provide information quickly is to use a multiuser system. To design this multiuser system using the main software Microsoft Visual FoxPro 9.0, and Microsoft Visual FoxPro 9.0 to manage the database. Therefore the final project entitled "Multiuser Based Value Data Processing Information System at STIKES Karya Husada Semarang" is an effective information system for delivering information at STIKES.